Жертовні тварини в поховальному обряді зарубинецької культури - Циндровська, Л.О. (Археологія, 1994)
Стаття присвячена маловивченому питанню жертвопринесення тварин під час поховального обряду в ранньослов'янський час на Середньому Подніпров’ї. В результате исследований ряда могильников зарубинецкой культуры на Северном Поднепровье было обнаружено значительное количество погребений, которые сопровождались костями животных, являющихся остатками погребальной пищи. В среднем число таких погребений составляло 40—50% общего числа захоронений. Анализ костей показал, что первое место среди жертвенных животных принадлежало мелкому рогатому скоту (овце или козе), второе — домашней свинье, третье — крупному рогатому скоту. Вопрос о жертвоприношениях пока мало изучен, но интересен для реконструкции идеологических представлений древнего населения Украины. A considerable amount of burials with bones of animals which were remains of the burial- rite food was found as a result of excavations of some barrows belonging to Zambinets culture in the mid Dnieper area. The number of such burials amounted on the average to 40—50% of the total number of burial places. An analysis of bones has shown that small cattle (ship or goat) ranks first among sacrificial animals, the second place is occupied by a pig, and the third by large cattle. The problem on sacrificesjs still scantily studied, though it is of great interest for reconstruction of ideological conceptions of ancient Ukrainian population.